Researching Organized Crime: A Novel Approach Combining Inductive and Storyline Paradigms - Felia Allum (International Journal of Qualitative Methods)
This article examines the methodological process employed in two recent research projects about mafias and organized crime groups (OCGs) and considers the self-reflexion that took place as part of the research process. Whereas most contemporary studies that focus on mafias and OCGs use theoretically informed approaches, which follow a hypothetical-deductive model, here a novel approach of combining an inductive model based on a Grounded Theory Method (GTM) with a storyline approach is presented. This results in perhaps a more thorough understanding of mafias and OCGs and produces a clear knowledge and evidence-based account of these realities that could be useful for practitioners. This article presents an innovative research design used in the general study of organized crime, the combination of a GTM with a storyline approach. Firstly, it explains the rationale and the steps involved in this combination. Secondly, its application in two specific research projects on organized crime is explained, empirically and theoretically. Thirdly, a critical reflection on the suitability of these two paradigms for the study of contemporary social phenomena is presented. Lastly, the conclusions suggest that while a GTM may be considered to lack positivist rigour, the contribution it makes to our understanding of mafias and OCGs must not be underestimated, in particular when combined with the storyline approach, which anchors evidence to theory.